Effect of the aging of titanium and zirconia abutment surfaces on the viability, adhesion, and proliferation of cells and the adhesion of microorganisms - Rigolin, Maria Sílvia Maurício [UNESP]; Barbugli, Paula Aboud [UNESP]; Jorge, Janaina Habib [UNESP]; Reis, Marina Rosa Delgado [UNESP]; Adabo, Gelson Luis [UNESP]; Casemiro, Luciana Assirati; Martins, Carlos Henrique Gomes; de Lima, Omar José; Mollo Junior, Francisco de Assis [UNESP] (Elsevier, 2019)
Statement of problem: The longevity of dental implants depends on the maintenance of peri-implant tissue and absence of inflammation. How the physical-chemical properties intrinsic to each material over time can affect adhesion, given constant cell turnover and biofilm development, remains unclear. Purpose: The purpose of this in vitro study was to evaluate the influence of aging on the viability, adhesion, and proliferation of normal oral keratinocytes (Nok-si) and on the multispecies biofilm formation of Fusobacterium nucleatum (F. nucleatum), Porphyromonas gingivalis (P. gingivalis), and Streptococcus sanguinis (S. sanguinis). Material and methods: Zirconia (ZrO2) and titanium (Ti) disks were analyzed by surface roughness, water contact angle, and X-ray diffraction before and after aging in an autoclave. The Nok-si cell viability was evaluated by using a 3-(4.5-dimethylthiazole-2-yl)2.5-diphenyl tetrazolium bromide assay (MTT), morphology by scanning electron microscopy (SEM), and proliferation and adhesion by using a confocal microscope. Multispecies biofilms were analyzed quantitatively by colony-forming units per milliliter (CFU/mL) and qualitatively by SEM. Results: For Ti, the aging process affected the roughness and wettability. However, for ZrO2, the aging did not affect roughness but did affect wettability and the ratio of the tetragonal to monoclinic phase (P<.05). A significant difference was found in the bacterial growth for Ti (nonaged and aged) in relation to the control, and no differences were found in Ti before and after aging; however, ZrO2 had increased growth of microorganisms after aging. For ZrO2, a statistically significant difference was found between aged ZrO2 and the control (P<.001). Conclusions: The results indicate that, after the aging, Ti showed better cell adhesion and proliferation and lower biofilm adhesion than zirconia.